Historical review, potential distribution, and conservation of the Mexican endemic rat Xenomys nelsoni (Rodentia: Cricetidae) - Ballesteros Barrera, Claudia; Zárate Hernández, Rocio; Vargas Miranda, Bárbara; Leyte-Manrique, Adrián; Elizalde-Arellano, Cynthia; Elizalde-Arellano, Cynthia; Martínez-Bernal, Angélica; Ortiz-Burgos, Selene (Revista de Biología Tropical, 2023)
Introduction: The Magdalena Rat, Xenomys nelsoni, is a rodent endemic to Mexico, whose distribution is restricted to dense tropical dry forests in a small region on the Pacific coast of Mexico. It is a poorly known species categorized as “Endangered” by the International Union for Conservation of Nature (IUCN). This lack of knowledge and the high rates of deforestation of its habitat makes its conservation a priority. Objective: To summarize the historical records deposited in scientific collections, to create potential distribution maps, and to analyze the conservation status of the species. Methods: We obtained species occurrence data from literature and digital databases, analyzing them by the decade. We used GARP and MaxEnt software to generate the ecological niche models. The importance of the variables in the model was estimated using the Jackknife technique. Results: Over 129 years, 19 collectors registered 69 specimens, of which 65 are deposited in one national and seven international collections. Although the species has only been collected in Jalisco and Colima, the potential distribution for X. nelsoni also includes the state of Michoacán. Of this estimated area, only 1.5 % is in a Protected Natural Area. Conclusions: The results of the potential distribution could be used to verify the presence of the species in places where it has not been collected, such as the northern part of the Chamela-Cuixmala Biosphere Reserve and in some areas of the physiographic province Costas del Sur in the state of Michoacán. It is needed to increase samplings in the least studied regions predicted by the model and expand the area of protection.